A STUDY OF THE DISTRIBUTION OF THE VESSELS AS A DIAGNOSTIC SIGN - Bardarov, Nikolai; Simeonova, Stilyana (Innovation in Woodworking Industry and Engineering design, 2018)
The distributi on of the vessels in wood is largely genetically staked for each species. Many of the features available are permanent and unique to each species. The size and density of the vessels depend to a large extent by the site conditions and the location in stem. The article examines the distribution of the vessels of some tropical tree species. The vessels were examined in cross-section. From the next few cells are formed the figures such as loops. Attitude lap / area (V/S) of these figures is discussed.